Affective Determinants of Mathematics Learning: A Literature Review - Travero, Arnel S.; Japos, Genaro V. (Future Science, 2024)
This study examined scientific articles as the basis for a literature review on affective determinants of mathematics learning. These af-fective determinants are the affective factors that are shown to affect mathematics learning, performance and achievements. The study used qualitative method using literature review that applies the con-tent of scientific articles from reputable databases such as ERIC, Web of Science, and PsycINFO. The findings indicate that students’ attitude towards mathematics, goal setting, motivation, self-concept, self-efficacy, self-regulated learning, and study habits significantly impact their mathematical performance and achievement, thereby influenc-ing their mathematics learning. However, the complex and bidirec-tional relationship between these factors and their influence on vari-ous factors, such as parental influences and teaching methods, remain unexplored. The study highlights the need for future research to in-vestigate these research gaps, providing a more comprehensive un-derstanding of the interplay between affective determinants and their impact on mathematics learning in diverse educational settings. Through addressing these gaps, researchers and educators can devel-op targeted interventions and strategies to enhance students’ math-ematical performance, achievement and overall learning experience.